SINERGITAS DINAS SOSIAL KOTA DENPASAR DENGAN KOMUNITAS PEDULI SKIZOFRENIA INDONESIA (KPSI) SIMPUL BALI DALAM PENANGANAN DISABILITAS MENTAL DI RUMAH BERDAYA KOTA DENPASAR - Pertiwi, Putu Rizki; Yasintha, Putu Nomy; Prabawati, Putu Anik (CITIZEN CHARTER, 2021)
Denpasar city as one of the cities contributes to the number of people with mental disabilities through the Denpasar City Social Service intensively making various efforts to handle mentally, especially schizophrenia with KPSI Simpul Bali by forming a treatment area in Denpasar City which is called Rumah Berdaya. The research uses descriptive qualitative research methods with data collection techniques in the form of observation, interviews and documentation. This study analyze the synergy between the Denpasar City Social Service and the KPSI Simpul Bali in Handling Mental Disabilities in Denpasar City Empowerment House, using synergy model according to Najiyati and Rahmat which consist of communication and coordination indicators. From research, it was found that synergy between the Denpasar City Social Service and KPSI Simpul Bali has been going well. But in its implementation there are still obstacles and several things that must be improved so that the synergy can be optimal. Keywords : Synergy, Mental Disabilities, Social Rehabilitation.